Optimal Activation of Reserves in Regional Balancing Markets - Petar Krstevski, Aleksandra Krkoleva Mateska, Rubin Taleski, Vesna Borozan (IET, 2022)
This paper presents a way for optimal usage of balancing energy from frequency regulation reserves in a regional balancing market. For this purpose, a modified method of optimal power flow calculation is proposed. This method enables more efficient usage of the transmission network capacities in the process of reserve activation on regional level, compared to the commonly used method of Common Merit Order List (CMOL) that considers only the available cross-zonal transmission capacity (CZC) and does not account the physical power flows. The paper also presents a simulation procedure for testing the proposed method on an IEEE test system with three zones
Keywords: REGIONAL BALANCING, OPTIMAL ACTIVATION OF BALANCING RESERVES